PENGARUH MODEL PEMBELAJARAN MASTERBERBASIS MIND MAPPINGTERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI SMAPEMBANGUNAN LABORATORIUM - Afifah Zafirah (Jurnal Edukasi dan Penelitian Matematika, 2020)
The ability to understand mathematical concepts is a foundation in the process of learning mathematics. For this reason, students need to master the concepts in learning mathematics. In fact, the ability to understand the concept of SMA Pembangunan Laboratorium UNP students is not optimal. This has a big effect on students to master other mathematical abilities. Therefore, efforts are needed in this matter. One of them uses the steps in the MASTER learning model based on mind mapping (Motivating your mind, Acquiring the information, Searching out the meaning, triggering the memory, Exhibiting what you know, and Reflecting how youve learned). This study aims to describe the differences in the ability to understand mathematical concepts of students who use the MASTER learning model with the ability to understand mathematical concepts of students who use conventional learning models. The research method used was quasi-experimental research design with Randomized Control-Group Only Design. Based on the results of this study concluded that the ability to understand mathematical concepts of students who use the MASTER learning model is better than the ability to understand mathematical concepts of students who use conventional learning models in class XI of SMA Pembangunan Laboratorium UNP. Keywords—Concept comprehension ability, MASTER based on mind mapping, Conventional learning